Resepsi Penonton terhadap Konflik Keluarga Film ‘Andai Ibu Tidak Menikah dengan Ayah’ - wafiq azizah ali; M. Fikri Akbar; Sandy Allifiansyah (CV. ITTC INDONESIA, 2025)
This study analyzes how viewers perceive family conflicts in the film Andai Ibu Tidak Menikah dengan Ayah (If Mom Hadn't Married Dad). The main focus of this analysis is the absent father figure, the mother's sacrifice, and the film's impact on children's mental health. The purpose of this study is to determine how viewers perceive the family conflicts depicted in the film. Qualitative methods were used to conduct a reception analysis using Stuart Hall's encoding/decoding model. This analysis was conducted through in-depth interviews with seven informants. Three types of audience positions were identified in this study: dominant-hegemonic, negotiated, and oppositional. The dominant-hegemonic position shows that the audience understands the film's message in accordance with the filmmaker's intentions, while the negotiated position shows that the audience provides critical interpretations. The film not only successfully conveys moral principles about sacrifice, responsibility, and the importance of family communication, but also encourages viewers to reflect on themselves.